2013
DOI: 10.1097/jom.0b013e3182973396
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Risk Perception and Biomarkers of Exposure in Florida Female Farmworkers

Abstract: Results showed that perceived pesticide exposure did not correspond to actual metabolite levels within differing agricultural subpopulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…The results of this study indicate that, despite the measures mandated by the WPS and some transition to non-anticholinesterase pesticides like pyrethroids, non-applicator farmworkers are still being exposed to pesticides. This is corroborated by studies in farmworker populations throughout the US documenting pesticide exposure through biomarkers, 3,9,20 as well as studies that show that WPS training is not always provided to workers, that growers are often not in compliance with laundry and bathing facilities and provision of personal protective equipment for workers to be able to practice WPS-recommended protective measures, and that farmworkers' need to work leads them to accept such circumstances. 3337 …”
Section: Discussionmentioning
confidence: 77%
“…The results of this study indicate that, despite the measures mandated by the WPS and some transition to non-anticholinesterase pesticides like pyrethroids, non-applicator farmworkers are still being exposed to pesticides. This is corroborated by studies in farmworker populations throughout the US documenting pesticide exposure through biomarkers, 3,9,20 as well as studies that show that WPS training is not always provided to workers, that growers are often not in compliance with laundry and bathing facilities and provision of personal protective equipment for workers to be able to practice WPS-recommended protective measures, and that farmworkers' need to work leads them to accept such circumstances. 3337 …”
Section: Discussionmentioning
confidence: 77%
“…[16][17][18] This community-based participatory research project and other recent studies have revealed that workplace heat is a concern for farmworkers. 5,19,20 The Centers …”
Section: From 2009 To 2013 the Fwaf Collaborated With Emorymentioning
confidence: 94%
“…High levels of pesticide exposure among migrant and seasonal farmworkers have been documented based on analysis of the dialkylphosphate (DAP) metabolites of OP insecticides 5,6 and of specific metabolites of OP, carbamate, and pyrethroid insecticides. 68 Recent analyses of the OP DAP metabolites indicate that Latino immigrant non-farmworkers also have high levels of detection and concentration for these metabolites, 5,9 indicating that they experience exposure to OP pesticides similar to that of Latino farmworkers.…”
Section: Introductionmentioning
confidence: 99%
“…68 Recent analyses of the OP DAP metabolites indicate that Latino immigrant non-farmworkers also have high levels of detection and concentration for these metabolites, 5,9 indicating that they experience exposure to OP pesticides similar to that of Latino farmworkers. These vulnerable US non-farmworker Latino populations had DAP metabolite concentrations higher than non-agricultural comparison groups in studies conducted outside of the US.…”
Section: Introductionmentioning
confidence: 99%